An Examination of Employment and Earning Outcomes of Probationers With Criminal and Substance Use Histories. (8th December 2015) - Chintakrindi, Sriram; Porter, Jeremy; Kim, Chunrye; Gupta, Suditi
There exists a strong relationship between having a criminal history and experiencing barriers to employment. Negative credentials facilitate the social and economic exclusion of individuals with criminal records. However, previous research has not concretely identified whether the stratification of economic opportunities by individual-level criminal records may be further affecting those who demonstrate substance use histories. In this study, we examine the substance use and criminal history profiles of probationers participating in an experimental drug treatment study and how probationer characteristics affect employment outcomes and gross earnings at both the 6- and 12-month follow-up periods. We hypothesize that substance use and criminal history have a main effect and interactional relationship that reduces the odds of self-reporting employment and decreases gross earnings outcomes of probationer. Our results demonstrate that substance use history and criminal history has a main effect on employment and earnings outcomes.